2010
DOI: 10.3109/00952991003736389
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Attrition from a National Sample of Methadone Maintenance Patients

Abstract: Background Methadone substitution therapy is an effective harm reduction treatment method for opioid dependent persons. Ability to retain patients in methadone treatment is an accepted predictor of treatment outcomes. Objectives The current study evaluates the roles of psychiatric comorbidity, medical comorbidity, and sociodemographic characteristics as predictors of retention in methadone treatment utilizing retrospective analysis of data from a nationwide sample of patients in methadone treatment in the VA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 39 publications
3
56
3
Order By: Relevance
“…Furthermore, most trauma treatment studies exclude patients with complex and severe presentations including those with suicidality (Roberts, Roberts, Jones, & Bisson, 2016), although the present study did not exclude any patients based on symptomatology or chronicity (Brand et al, 2009). Attrition is higher in patients who have low incomes, receive government subsidies, and who struggle with substance abuse and/or serious psychiatric illnesses (Mancino et al, 2010), characteristics that were common in this sample (Brand et al, 2009). Although data regarding reasons for attrition were not collected, in cases where patients terminated their treatment with the therapist (and thus the study), therapists indicated reasons such as objective causes (e.g.…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, most trauma treatment studies exclude patients with complex and severe presentations including those with suicidality (Roberts, Roberts, Jones, & Bisson, 2016), although the present study did not exclude any patients based on symptomatology or chronicity (Brand et al, 2009). Attrition is higher in patients who have low incomes, receive government subsidies, and who struggle with substance abuse and/or serious psychiatric illnesses (Mancino et al, 2010), characteristics that were common in this sample (Brand et al, 2009). Although data regarding reasons for attrition were not collected, in cases where patients terminated their treatment with the therapist (and thus the study), therapists indicated reasons such as objective causes (e.g.…”
Section: Discussionmentioning
confidence: 93%
“…Numerous factors have been found to influence retention in MMT, most prominently higher methadone dose and particular patient characteristics (e.g., older age; Mancino et al 2010;Strike et al 2005). The present study examined the relationship between continued drug use and rates of MMT retention.…”
Section: Discussionmentioning
confidence: 97%
“…Numerous studies have since confirmed the relationship between duration of MMT and both positive long-term patient outcomes and increased vulnerability for a recurrence of opioid addiction following MMT cessation (Kimber et al 2010;Dole 1994). Studies of first-year attrition in MMT reveal high dropout rates, frequently in the 50%+ range (Bell et al 2006;Deck & Carlson 2005;Simpson et al 1997), with some studies noting one-year attrition at close to 80% (Mancino et al 2010).…”
Section: Mmt Retentionmentioning
confidence: 99%
“…Otherwise, there is no clear pattern or association between predictors and treatment retention. For example, Mancino et al (2010), found that age, the presence of a serious mental illness, and race/ethnicity were associated with treatment retention. According to Fischer, Vasdev, Haydon, Baliunas, & Rehm, (2005), study site, housing status, alcohol use, and the use of heroin or injection drugs were related to engagement in treatment, but age and depression were not.…”
Section: Introductionmentioning
confidence: 99%